Relatedness of Indian flax genotypes (Linum usitatissimum L.): an inter-simple sequence repeat (ISSR) primer assay - Rajwade, Ashwini V.; Arora, Ritu S.; Kadoo, Narendra Y.; Harsulkar, Abhay M.; Ghorpade, Prakash B.; Gupta, Vidya S. (Molecular Biotechnology, 2010)
The objective of this study was to analyze the genetic relationships, using PCR-based ISSR markers, among 70 Indian flax (Linum usitatissimum L.) genotypes actively utilized in flax breeding programs. Twelve ISSR primers were used for the analysis yielding 136 loci, of which 87 were polymorphic. The average number of amplified loci and the average number of polymorphic loci per primer were 11.3 and 7.25, respectively, while the percent loci polymorphism ranged from 11.1 to 81.8 with an average of 63.9 across all the genotypes. The range of polymorphism information content scores was 0.03-0.49, with an average of 0.18. A dendrogram was generated based on the similarity matrix by the Unweighted Pair Group Method with Arithmetic Mean (UPGMA), wherein the flax genotypes were grouped in five clusters. The Jaccard's similarity coefficient among the genotypes ranged from 0.60 to 0.97. When the omega-3 alpha linolenic acid (ALA) contents of the individual genotypes were correlated with the clusters in the dendrogram, the high ALA containing genotypes were grouped in two clusters. This study identified SLS 50, Ayogi, and Sheetal to be the most diverse genotypes and suggested their use in breeding programs and for developing mapping populations.
Keywords: ALA; Alpha linolenic acid; Diversity assessment; Linseed; Oil content; Omega-3 fatty acid

Genome-wide identification and characterization of microRNA genes and their targets in flax (Linum usitatissimum) - Barvkar, Vitthal T.; Pardeshi, Varsha C.; Kale, Sandip M.; Qiu, Shuqing; Rollins, Meaghen; Datla, Raju; Gupta, Vidya S.; Kadoo, Narendra Y. (Planta, 2013)
MicroRNAs (miRNAs) are small (20-24 nucleotide long) endogenous regulatory RNAs that play important roles in plant growth and development. They regulate gene expression at the post-transcriptional level by translational repression or target degradation and gene silencing. In this study, we identified 116 conserved miRNAs belonging to 23 families from the flax (Linum usitatissimum L.) genome using a computational approach. The precursor miRNAs varied in length; while most of the mature miRNAs were 21 nucleotide long, intergenic and showed conserved signatures of RNA polymerase II transcripts in their upstream regions. Promoter region analysis of the flax miRNA genes indicated prevalence of MYB transcription factor binding sites. Four miRNA gene clusters containing members of three phylogenetic groups were identified. Further, 142 target genes were predicted for these miRNAs and most of these represent transcriptional regulators. The miRNA encoding genes were expressed in diverse tissues as determined by digital expression analysis as well as real-time PCR. The expression of fourteen miRNAs and nine target genes was independently validated using the quantitative reverse transcription PCR (qRT-PCR). This study suggests that a large number of conserved plant miRNAs are also found in flax and these may play important roles in growth and development of flax.
Keywords: Digital expression analysis; Gene cluster; Linseed; miRNA; MiRNA target transcript; Promoter analysis

Differential transcriptional activity of SAD, FAD2 and FAD3 desaturase genes in developing seeds of linseed contributes to varietal variation in alpha-linolenic acid content - Rajwade, Ashwini V.; Kadoo, Narendra Y.; Borikar, Sanjay P.; Harsulkar, Abhay M.; Ghorpade, Prakash B.; Gupta, Vidya S. (Phytochemistry, 2014)
Linseed or flax (Linum usitatissimum L.) varieties differ markedly in their seed a-linolenic acid (ALA) levels. Fatty acid desaturases play a key role in accumulating ALA in seed. We performed fatty acid (FA) profiling of various seed developmental stages of ten Indian linseed varieties including one mutant variety. Depending on their ALA contents, these varieties were grouped under high ALA and low ALA groups. Transcript profiling of six microsomal desaturase genes (SAD1, SAD2, FAD2, FAD2-2, FAD3A and FAD3B), which act sequentially in the fatty acid desaturation pathway, was performed using real-time PCR. We observed gene specific as well as temporal expression pattern for all the desaturases and their differential expression profiles corresponded well with the variation in FA accumulation in the two groups. Our study points to efficient conversion of intermediate FAs [stearic (SA), oleic (OA) and linoleic acids (LA)] to the final product, ALA, due to efficient action of all the desaturases in high ALA group. While in the low ALA group, even though the initial conversion up to OA was efficient, later conversions up to ALA seemed to be inefficient, leading to higher accumulation of OA and LA instead of ALA. We sequenced the six desaturase genes from the ten varieties and observed that variation in the amino acid (AA) sequences of desaturases was not responsible for differential ALA accumulation, except in the mutant variety TL23 with very low (<2%) ALA content. In TL23, a point mutation in the FAD3A gene resulted into a premature stop codon generating a truncated protein with 291 AA. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: ALA; Fatty acid desaturases; Fatty acids; Flax; Gene expression; Linseed